A Study on Dead-beat Predictive Voltage Control Strategy for DC Microgrid System of New Energy Cruise Ship - LIANG Xifan; WANG Yue; FU Jianguo; ZHOU Zhenbang; TONG Ziwei (Kongzhi Yu Xinxi Jishu)
DC microgrid systems based on hybrid photovoltaic-electrical energy storage systems for power generation are widely used in new energy cruise ships. For the problem of power supply voltage unbalance arising when a daily load power supply converter is connected to an unbalanced load or single-phase load, this paper proposes a dead-beat predictive voltage control strategy based on positive and negative sequence separation of output voltage. This strategy can realize control of positive and negative sequence components of the power supply converter voltage under the positive and negative sequence coordinate systems respectively, to ensure the three-phase voltage balance of the power supply converter, enhance the anti-interference ability of the system against unbalanced load and avoid additional power quality control devices. The simulation results show that, after the proposed control strategy is adopted, the voltage unbalance of the daily load power supply converter is reduced from 28% to less than 0.5%, which verifies the effectiveness of the proposed control algorithm .